Use of black soldier fly larvae and freshwater shrimp to partly substitute commercial diet for Nile tilapia cultured in smallholder fish farms – A case study in Busia County, Kenya - Kals, Jeroen; Opiyo, Mary A.; Rurangwa, Eugene; Soma, Katrine; Ndambi, Asaah; Vernooij, Adriaan (Frontiers in Sustainable Food Systems, 2024)
Fish-farming in Kenya is challenged by the availability and high cost of feed ingredients, especially protein sources. Using black soldier fly larvae (Hermetia illucens) (BSFL) directly or indirectly as a feed ingredient to feed fish is interesting as they efficiently convert organic wastes into high-quality proteins. In addition, the freshwater shrimp (Caridina nilotica) (CN), an important by-catch of the silver cyprinid (Rastrineobola argentea) fisheries in Lake Victoria, could be another alternative protein source. Therefore, this study determined whether dried BSFL or dried CN could partly substitute the commercial diet when growing Nile tilapia (Oreochromis niloticus) in a smallholder farm aggregated in an aquapark. The nutritional values and cost-effectiveness of the alternative feeding strategies were compared to commercial diet (CD) only. During an 84-day experimental period, Nile tilapia were fed one of the three feeding strategies, including the use of only the commercial diet , to be compared with diets replacing 20% of the commercial diet with BSFL and or CN. The fish were fed to apparent satiation twice a day. At the end of the trial, biomass, the number of fish, growth, survival rate, total fish production, economic feed conversion rate and productivity per pond, were determined. As such, Body Weight (BW ) was similar between across feeding strategies (P > 0.05), measured 63.2±3.9, 68.0±7.4 and 68.0±7.4g for fish-fed diets with CD, BSFL and CN, respectively. Hence, nutritionally and from a production point of view, the three feeding strategies used in this study performed equally well. Notably, the use of BSFL led to a significantly higher economic return (P < 0.05) compared to the use of CN and commercial diet alone. The trials in this study demonstrate that BSFL and CN can be used to partly susubstitutepplement commercial diet . In addition, the trial show that the use of BSFL as a to partly substitute the commercial diet can boost sustainable fish production in a smallholder farm set-up aggregated in an aquapark.